GAFF-AIC: reoptimisation of the GAFF force field for realistic densities and viscosities in aromatic isocyanates - Deshmukh, Vaibhav Arun; Kühne, Thomas D.; Gamez, Jose A. (Molecular Simulation, 2023)
Molecular mechanical force field methods, which help to investigate material properties beyond molecular scales, describe the intra- and intermolecular interactions of molecules assuming a classical force field comprised of several terms. Force fields should accurately describe the energy interactions of all moleculer elements to, eventually, accurately reproduce macromolecular properties of that materials. In the case of aromatic isocyanates, general purpose force fields failed to properly account for molecular interactions and, consequently, at the prediction of macromolecular properties of isocyanate-based materials. The present study presents a new force field based on the General AMBER Force Field (GAFF), namely GAFF-AIC, which shows improved results for the prediction of macromolecular properties, in particular density and viscosities, of materials based on aromatic isocyanates. For that, a new set of parameters for intramolecular and intermolecular interactions has been optimised by means of a least square fitting. It is shown that GAFF-AIC is able to accurately reproduce the experimental density and viscosity of liquid 1-naphtyl isocyanate. Moreover, these newly proposed force field parameters were evaluated to see how efficient they were at predicting the liquid densities and viscosities for several considered aromatic isocyanates, resulting in an accurate estimation that is in excellent agreement with experimental results.
CRIS-Team Scopus Importer:2023-03-20
Keywords: computational simulations; force field parametrisation; General Amber Force Field; isocyanates; Molecular dynamics